Constrained control of wind turbines for power regulation in full load operation - Habibi, H.; Nohooji, H.; Howard, Ian (IEEE, 2018)
© 2017 IEEE. The safe operation of wind turbines is a vital criterion which should be considered in the controller design to avoid rotor over speeding and hazardous operation. In this regard, the main focus of this paper is to keep the wind turbine operating within given limits by considering constrained control concepts using the barrier Lyapunov function. The nonlinear model of a benchmark wind turbine is considered and the wind speed variation is assumed to be unmeasurable disturbance and consequently, utilising the radial basis function neural network, an aerodynamic torque estimator is designed. The proposed controller is evaluated via numerical simulations and its performance is compared to a practical industrial wind turbine controller and a quadratic Lyapunov-based controller.